1991
DOI: 10.1002/clc.4960140806
|View full text |Cite
|
Sign up to set email alerts
|

Changes in left atrial size in patients with lone atrial fibrillation

Abstract: Summary: A retrospective analysis was performed on 23 subjects with lone atrial fibrillation who were followed for an average of 6.2 years (1.1 -12.8 years). In all patients, underlying organic heart disease was excluded based on history. physical exam, electrocardiogram, echocardiogram, and Doppler ultrasound interrogation. All patients had at least two echocardiographic studies during the period of observation. Atrial fibrillation was chronic in 1 I subjects and paroxysmal in 12. All echocardiographic measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 12 publications
6
18
0
1
Order By: Relevance
“…This supports the hypothesis that LA enlargement occurs only if AF becomes chronic [30,31]. Moreover, Suarez et al [32] reported that paroxysmal AF may induce slowly progressive LA enlargement. In addition, Kallmünzer et al [33] recently demonstrated that the risk of significant cardiac arrhythmia after an acute cerebrovascular event is highest during the first 24 h of care and then progressively declines over the first 3 days.…”
Section: Discussionsupporting
confidence: 70%
“…This supports the hypothesis that LA enlargement occurs only if AF becomes chronic [30,31]. Moreover, Suarez et al [32] reported that paroxysmal AF may induce slowly progressive LA enlargement. In addition, Kallmünzer et al [33] recently demonstrated that the risk of significant cardiac arrhythmia after an acute cerebrovascular event is highest during the first 24 h of care and then progressively declines over the first 3 days.…”
Section: Discussionsupporting
confidence: 70%
“…These data suggest that, by valuing the type of AF over LA volume, we may be targeting patients who are in fact less likely to benefit from PV isolation than others in whom therapy is withheld due to efficacy concerns. Since LA dilatation tends to progress over time [36,37], our results also indirectly support earlier intervention in patients with symptomatic AF, backing the concept of a 'window of opportunity' for effective rhythm control therapy [1,38]. Finally, these results highlight the difficulties in predicting the long term outcome of PVI.…”
Section: Study Limitationssupporting
confidence: 59%
“…The role of the AF on changes in LA dimension was addressed in previous studies [5,16,17]. In heterogeneous cohorts, LA size was related to the duration of the arrhythmia and increased during a follow-up period.…”
Section: Discussionmentioning
confidence: 98%